Evolution of Pb-Free and Partially Pb-Substituted Perovskite Absorbers for Efficient Perovskite Solar Cells - Wadi M.A.A.; Chowdhury T.H.; Bedja I.M.; Lee J.-J.; Amin N.; Aktharuzzaman M.; Islam A. (The Korean Institute of Metals and Materials, 2023)
Convergence of numerical methods; Efficiency; Metal ions; Metals; Perovskite; Photovoltaic effects; Solar absorbers; Solar power generation; Toxicity; Degradation effect; Optimal performance; Partial replacement; Pb-free; Perovskite compounds; Photovoltaic performance; Photovoltaic technology; Power conversion efficiencies; Perovskite solar cells